Risk factors for poor outcomes in Indonesian children with Guillain-Barré syndrome - Gunawan, Prastiya Indra; Noviandi, Riza; Samosir, Sunny Mariana (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Guillain-Barré syndrome (GBS) is a rare disease in which the immune system strikes the peripheral nervous system. Lack of observation may lead to respiratory failure or even death. This study aims to analyse risk factors for poor outcomes in children with GBS especially in limited resource settings.Methods: This was a retrospective study using medical records conducted on children with GBS. Data obtained included age, sex, clinical symptoms, infection history, laboratory examination, Medical Research Council (MRC) scale, treatment, GBS type, the use of mechanical ventilation, GBS disability score, and outcome recorded in the medical history. The outcomes obtained during treatment in this study were categorised as recovery or mild disability and poor outcome based on GBS disability level. Statistical analysis used a chi-squared, multivariate logistic regression test with a significance score of p < 0.05.Results: There were 61 children with GBS fulfilling inclusion criteria during the study. The frequency of male children was 54.1% and respiratory infection was the most antecedent event in 45 cases (73.8%). The mean age 8.4 years old (± 3.79), and the most common type of GBS was acute inflammatory demyelinating polyneuropathy (AIDP) in 89.1% cases. The most common GBS treatment was a combination of intravenous immunoglobulin (IVIg) and steroids, and a poor outcome was observed in 80.3% of children with GBS. Age, sex, clinical manifestation, laboratory examination, antecedent event, MRC scale, and GBS type were not risk factors of poor outcomes in GBS.Conclusions: Mechanical ventilation was related to poor outcomes in children with GBS (OR = 0.112, 95% CI = 0.013-0.932, p